let-7-Complex MicroRNAs Regulate Broad-Z3, Which Together with Chinmo Maintains Adult Lineage Neurons in an Immature State. - Wu, Y.C.; Chawla, G.; Sokol, N. (G3 : genes - genomes - genetics, 2020)
During Drosophila melanogaster metamorphosis, arrested immature neurons born during larval development differentiate into their functional adult form. This differentiation coincides with the downregulation of two zinc-finger transcription factors, Chronologically Inappropriate Morphogenesis (Chinmo) and the Z3 isoform of Broad (Br-Z3). Here, we show that br-Z3 is regulated by two microRNAs, let-7 and miR-125, that are activated at the larval-to-pupal transition and are known to also regulate chinmo The br-Z3 3'UTR contains functional binding sites for both let-7 and miR-125 that confers sensitivity to both of these microRNAs, as determined by deletion analysis in reporter assays. Forced expression of let-7 and miR-125 miRNAs leads to early silencing of Br-Z3 and Chinmo and is associated with inappropriate neuronal sprouting and outgrowth. Similar phenotypes were observed by the combined but not separate depletion of br-Z3 and chinmo Because persistent Br-Z3 was not detected in let-7-C mutants, this work suggests a model in which let-7 and miR-125 activation at the onset of metamorphosis may act as a failsafe mechanism that ensures the coordinated silencing of both br-Z3 and chinmo needed for the timely outgrowth of neurons arrested during larval development. The let-7 and miR-125 binding site sequences are conserved across Drosophila species and possibly other insects as well, suggesting that this functional relationship is evolutionarily conserved.